FBN1 contributing to familial congenital diaphragmatic hernia. - Beck, Tyler F; Campeau, Philippe M; Jhangiani, Shalini N; Gambin, Tomasz; Li, Alexander H; Abo-Zahrah, Reem; Jordan, Valerie K; Hernandez-Garcia, Andres; Wiszniewski, Wojciech K; Muzny, Donna; Gibbs, Richard A; Boerwinkle, Eric; et al. (Am J Med Genet A, 2015)
Congenital diaphragmatic hernia (CDH) is a relatively common, life--threatening birth defect. We present a family with recurrent CDH--paraesophageal and central--for whom exome sequencing (ES) revealed a frameshift mutation (c.4969_4970insA, p.Ile1657Asnfs*30) in the fibrillin 1 gene (FBN1) that causes Marfan syndrome. A diagnosis of Marfan syndrome had not been considered previously in this family. However, a review of the literature demonstrated that FBN1 mutations have an unusual pattern of CDH in which paraesophageal hernias are particularly common. Subsequent clinical evaluations revealed evidence for ectopia lentis in affected family members supporting a clinical diagnosis of Marfan syndrome. Since only two other cases of familial CDH have been described in association with FBN1 mutations, we investigated an oligogenic hypothesis by examining ES data for deleterious sequence changes in other CDH-related genes. This search revealed putatively deleterious sequence changes in four other genes that have been shown to cause diaphragm defects in humans and/or mice--FREM1, DES, PAX3 and MET. It is unclear whether these changes, alone or in aggregate, are contributing to the development of CDH in this family. However, their individual contribution is likely to be small compared to that of the frameshift mutation in FBN1. We conclude that ES can be used to identify both major and minor genetic factors that may contribute to CDH. These results also suggest that ES should be considered in the diagnostic evaluation of individuals and families with CDH, particularly when other diagnostic modalities have failed to reveal a molecular etiology.
Keywords: Adult; Child, Preschool; DNA Mutational Analysis; Exome; Female; Fibrillin-1; Fibrillins; Frameshift Mutation; Genetic Association Studies; Hernias, Diaphragmatic, Congenital; Humans; Male; Marfan Syndrome; Microfilament Proteins; Pedigree

Loss-of-function mutations in TGFB2 cause a syndromic presentation of thoracic aortic aneurysm. - Lindsay, Mark E; Schepers, Dorien; Bolar, Nikhita Ajit; Doyle, Jefferson J; Gallo, Elena; Fert-Bober, Justyna; Kempers, Marlies J E; Fishman, Elliot K; Chen, Yichun; Myers, Loretha; Bjeda, Djahita; Oswald, Gretchen; et al. (Nat Genet, 2012)
Loeys-Dietz syndrome (LDS) associates with a tissue signature for high transforming growth factor (TGF)-β signaling but is often caused by heterozygous mutations in genes encoding positive effectors of TGF-β signaling, including either subunit of the TGF-β receptor or SMAD3, thereby engendering controversy regarding the mechanism of disease. Here, we report heterozygous mutations or deletions in the gene encoding the TGF-β2 ligand for a phenotype within the LDS spectrum and show upregulation of TGF-β signaling in aortic tissue from affected individuals. Furthermore, haploinsufficient Tgfb2(+/-) mice have aortic root aneurysm and biochemical evidence of increased canonical and noncanonical TGF-β signaling. Mice that harbor both a mutant Marfan syndrome (MFS) allele (Fbn1(C1039G/+)) and Tgfb2 haploinsufficiency show increased TGF-β signaling and phenotypic worsening in association with normalization of TGF-β2 expression and high expression of TGF-β1. Taken together, these data support the hypothesis that compensatory autocrine and/or paracrine events contribute to the pathogenesis of TGF-β-mediated vasculopathies.
Keywords: Animals; Aortic Aneurysm, Thoracic; Disease Models, Animal; Female; Fibrillin-1; Fibrillins; Haploinsufficiency; Humans; Loeys-Dietz Syndrome; Male; Marfan Syndrome; Mice; Mice, Knockout; Mice, Mutant Strains; Microfilament Proteins; Mutation; Pedigree; Phenotype; Signal Transduction; Syndrome; Transforming Growth Factor beta2